A veces me siento así - Altamirano Herrera, Cesarina (2019)
The present demonstrative session of learning called “Sometimes I feel like that” for boys and girls of 3 years from initial education level belonging to a Regular Basic Education has like learning purpose the development of the competence of “Build their identity” and the capacity self-regulates their emotions._x000D_ It answers itself to the performance “Express their emotions; They use for it facial expressions and corporal motions and words. They identify their emotions and the ones that they observe in the others when the adult names it”_x000D_ The class is based in social-constructivist theories in the frame of the National curriculum for competences, considering pedagogic processes of the area of the Civic training and with emphasis in the formative evaluation.